Social impacts of events and the role of anti-social behaviour - Deery, Margaret; Jago, L. (Emerald Group Publishing Limited, 2010)
Purpose – The research focusing on the social impacts of events on communities has reached a level of critical mass and this paper aims to synthesise the literature, including the research methods used and analytical techniques that have been employed in order to provide a platform for future research in this important area. Design/methodology/approach – The key method used is a literature review of all the available academic research into the social impacts of events on communities and the development of a model for future research. Findings – After reviewing the social impact literature, the paper finds that one negative social impact, in particular, has the potential to undermine the key positive impacts that events can deliver for a host community. This impact, which is collectively known as anti-social behaviour (ASB) incorporates behaviour such as drunken, rowdy and potentially life and property threatening behaviour. Research limitations/implications – The consequences of the impact of ASB are so serious, partly because it is an impact which the media often highlight, can seriously tarnish the image of an event in the eyes of the local community and reduce their pride in the destination. Community tourism leaders need to manage this impact in order to maintain resident support. The paper concludes with a model for future research into the social impacts of events on communities, focusing on the role that ASB plays in residents’ perceptions of events. Originality/value – This paper provides a review of the literature on social impacts to date and is a resource for researchers in the area. In addition, the paper highlights the role that ASB plays in aggravating negative perceptions of tourism in communities and the need for a more in-depth understanding of ASB.